(untitled) (Research, Society and Development, 2022)
Type 1 diabetes mellitus is the second most common chronic disease and endocrine-metabolic disorder in childhood. It has been increasingly diagnosed in children, due to the broad spectrum of screening. It is estimated a prevalence between 1.1 to 1.4/1000 children under 15 years of age. Such a situation can affect the quality of life of children and family members. Environmental factors can influence this factor. Age, sex, type of health insurance have a statistically significant association with better quality of life. Maternal education, maternal marital status, insulin regimen and glycemic control modify maternal-infant quality of life. The mean age of onset of the disease is 8.8 years, debuting with diabetic ketoacidosis. Glycosylated hemoglobin (HbA1c) is the other point of change. High levels are obtained in both adherence and quality of life. Quality of life is associated with the use of a continuous glucose monitoring system to avoid less severe hypoglycemia and renal complications. Faced with such a situation, the objective is to carry out a literature review on the subject to assess the impact of DM1 and its repercussions on the child’s life. Thus, it can be seen that it has had a direct impact on the lives of both the family and the child, especially in the acceptance of the new lifestyle. Therefore, studies are essential to analyze the benefits of improving the quality of life with the support of the multidisciplinary team.